Career Support and Its Effectiveness in Technical Intern Training Program for Farm Work Contracts: A Case Study of Japan Agricultural Cooperatives in Kagoshima Prefecture - Nakahara, Hiroko; Nakatsuka, Masaya (Journal of Rural Problems, 2024)
Acceptance of technical intern trainees is expanding due to the agricultural labor shortage. Career development is a significant issue for trainees; however, how to provide effective career support remains unclear. In particular, the fact that outsourced contracting involves repetitive work is disadvantageous for skill acquisition, making career support even more critical. This study, conducted through interviews with one JA (Japan Agricultural Cooperatives) in Kagoshima Prefecture, found that JA actively provided career support, such as Japanese language learning support and career aspirations interviews. The technical intern trainees generally evaluated the JA’s career support positively. The findings suggest that JA’s career support effectively aids skill acquisition and career advancement, potentially leading to the retention of motivated trainees.